Rola fotografii w komunikowaniu politycznym na przykładzie „portretu podwójnego” Lecha i Marii Kaczyńskich - Mateja, Magdalena (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2012)
The catastrophe in Smoleńsk has significantly affected the image of Lech Kaczyński presented in the media, which has quite clearly translated into social opinions. Words of praise for his presidency and remarks that he had been underestimated became increasingly frequent. The picture of Mr and Mrs Kaczyński therefore became a tool for generating a new image of the President, facilitating a kind of posthumous ‘rebranding’. This image breakthrough provided the Law and Justice (PiS) party with the ‘added value’ of the sympathy of most of the media and the social trust Maria Kaczyńska enjoyed before and after April 10, 2010, in contrast to her husband. The ‘double portrait,’ multiplied by the press at the time of national mourning, later became an expression of an affirmative approach extended to a defined political circle. It is not surprising then that PiS, which has emphasized the value of ‘Lech Kaczyński’s testament’ and assumed the role of the depositary of his policy, has utilized the photography of the presidential couple (and their biographies) on many occasions.